Hormonal induction of Dopa decarboxylase in the epidermis of Drosophila is mediated by the Broad-Complex. - Hodgetts, R.B.; Clark, W.C.; O'Keefe, S.L.; Schouls, M.; Crossgrove, K.; Guild, G.M.; von Kalm, L. (Development, 1995)
The 2B5 early puff locus corresponds to the Broad-Complex BR-C) and encodes a family of transcription factors whose members are induced by the molting hormone ecdysone. Mutations in the br subcomplementation group substantially reduce the levels of Dopa decarboxylase (DDC) in the epidermis of mature third instar larvae but not in mature second instar organisms. Enzyme levels are normal in the central nervous system of the two mutants examined. The specificity of these effects suggests that a product of the BR-C locus mediates the rapid appearance of DDC in mature third instar larvae experiencing an elevated titer of ecdysone. The likely identity of this protein has been confirmed by pursuing the observation that the br28 allele caused by the insertion of a P element into the Z2 DNA-binding domain. Both the transcript and a protein carrying this domain are present in the epidermis and a BR-C recombinant protein carrying the Z2 finger binds to the first intron of the Ddc gene. Five binding sites have been identified within the intron by DNAase I footprinting and a core consensus sequence has been derived which shares some identity with the consensus binding site of the Z2 protein to the Sgs-4 regulatory region. Our demonstration that Ddc is a target of BR-C in the epidermis is the first direct evidence of a role for this early gene in a tissue other than the salivary glands. The data reinforce the idea that BR-C, which clearly mediates a salivary gland-specific response to ecdysone, may play a widespread role in the hormone's activation of gene cascades in other target tissues.